Androgen receptor distribution in the rat prostate gland and seminal vesicles - Gur, F. M.; Timurkaan, S. (Czech Academy Agricultural Sciences, 2016)
To better understand the effect of androgen on the growth and function of accessory sex glands, it can be useful to determine the presence or absence of the androgen receptor (AR) in the individual cell types. Five adult intact male rats were sacrificed at 120 days. Their seminal vesicles and prostate glands were removed, fixed in Bouin's fixative and embedded in paraffin wax. The tissues were sectioned at 5 mu m and stained using the microwave-stimulated antigen retrieval technique for immunohistochemistry. Positive immunohistochemical staining for the AR was evident in nuclei but not in the cytoplasm of gland cells such as luminal cells, basal cells, periacinar smooth muscle cells, other stromal cells, and smooth muscle cells in the tunica muscularis. The proportions of AR-positive and AR-negative basal cells were similar. The staining intensity of luminal cells was greater than basal cells and stromal cells. The numbers of AR-positive and AR-negative luminal cells in the prostate were almost equal. On the other hand, in the seminal vesicle only a small number of luminal cells were AR-negative. These observations can be interpreted to mean that the epithelium of the seminal vesicle is more sensitive to androgenic stimulation than the prostate epithelium.
Keywords: prostate; seminal vesicle; androgen receptor; immunohistochemistry; rat